Threatened Species Legislation 2004
DOI: 10.7882/fs.2004.063
|View full text |Cite
|
Sign up to set email alerts
|

Case studies in implementing the NSWThreatened Species Conservation Act1995 for invertebrate conservation

Abstract: The difficulties in applying threatened species legislation, which has a general vertebrate and vascular plant focus, to invertebrates, have been widely recognised. Nevertheless, such legislation provides valuable opportunities to promote invertebrate conservation that were previously available only for high profile, charismatic vertebrate species. This paper presents three case studies, two land snails Lord Howe Placostylus Placostylus bivaricosus and Mitchell's Rainforest Snail Thersites mitchellae, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, in this review we bring together information presented in a series of unpublished technical reports to government authorities in New Caledonia, particularly those concerning P. fibratus (Pöllabauer 1994(Pöllabauer , 1995Brescia 1997Brescia , 1999Brescia , 2000Brescia , 2001Brescia , 2002Brescia , 2003Brescia , 2004Brescia , 2005Brescia , 2007 and P. porphyrostomus Pöllabauer 2004, 2005). Some additional inferences can be made from studies on the New Zealand endemic Placostylus species (Choat and Schiel 1980;Penniket 1981;Brook and Laurenson 1992;Sherley et al 1998;Stringer et al 2004) and on the one species of Placostylus on Lord Howe Island (Murphy and Nally 2004).…”
Section: Life Historymentioning
confidence: 99%
See 4 more Smart Citations
“…However, in this review we bring together information presented in a series of unpublished technical reports to government authorities in New Caledonia, particularly those concerning P. fibratus (Pöllabauer 1994(Pöllabauer , 1995Brescia 1997Brescia , 1999Brescia , 2000Brescia , 2001Brescia , 2002Brescia , 2003Brescia , 2004Brescia , 2005Brescia , 2007 and P. porphyrostomus Pöllabauer 2004, 2005). Some additional inferences can be made from studies on the New Zealand endemic Placostylus species (Choat and Schiel 1980;Penniket 1981;Brook and Laurenson 1992;Sherley et al 1998;Stringer et al 2004) and on the one species of Placostylus on Lord Howe Island (Murphy and Nally 2004).…”
Section: Life Historymentioning
confidence: 99%
“…On Lord Howe Island, Murphy and Nally (2004) found P. bivaricosus (Gascoin, 1854) under well-developed, moisture-retaining leaf litter in evergreen closed forest, often, but not exclusively, in the vicinity of Banyan Figs (Ficus macrophylla columnaris Moore & Mueller 1874). These authors also observed that P. bivaricosus was sparse or absent in areas developed as palm plantations, but mixed palm and broad-leaf forest provided good habitat.…”
Section: Distribution Habitat and Dietmentioning
confidence: 99%
See 3 more Smart Citations